EFEITO DO ENRIQUECIMENTO SONORO SOBRE RESPOSTAS FACIAIS E FISIOLÓGICAS DE CAVALOS CASTRADOS E ÉGUAS DA RAÇA PANTANEIRA SOB ESTRESSE DE CURTA DURAÇÃO - VANESSA CRISTINI SEBASTIÃO DA FÉ (2024)
The research was carried out with the objective of evaluating auditory stimuli for horses during social isolation and movement restrictions, and their ability to promote the reduction of stress responses. In chapter 1, there is a literature review, which initially addressed the chal-lenges faced in the domestic environment, as well as non-invasive indicators of stress, and later, on sound enrichment in the animal production scenario as a way of promoting quality of life and ensuring the well-being, especially of those raised in an intensive system. Perception and hearing capacity in horses have been reported, thus verifying the potential effect of music on the species. Chapter 2 is the article in which horses of the Pantaneira breed (n=8) were evaluated, consisting of experiment I (4 females) and experiment II (4 castrated males) in a 4x4 Latin square design with experimental treatment – musical genre (classical (classical) Beethoven's 9th symphony), country (Rablin in my shoes by Hank Williams Jr) and new age (Horsing around by Janet Marlow)) and control (no music). Each individual was taken individually to a containment trunk, and subsequently administered the experimental treatment for approximately 24 minutes. Physiological parameters (heart rate, heart rate variability, respiratory rate, eye temperature and surface temperature) as well as facial expressions were recorded. During collections, microclimatic parameters were also monitored to characterize the environment. The songs 9th Symphony by Beethoven (classical genre) and Rablim in my shoes by Hank Williams Jr (country genre) promote stress reduction and a consequent relaxation effect in females during social isolation and movement restrictions. The horses expressed a less pro-nounced response, demonstrating a possible preference for the song Horses around by Janet Marlow (new age genre), under the same handling conditions. Music can be used as sound enrichment for Pantaneira horses in the specific circumstances of the present work, and it is important to consider the musical genre, sex, breed, handling and exposure time.